Analisis Kepribadian dan Gaya Komunikasi Dalam Negosiasi Bisnis - Fina Abiyya Agustin Mubarokah; Hawa Arofah Qudsy; Zalfa Putri Salsabila; Maura Azzakiyah Basya; Lilik Sumarni (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
This research aims to analyze personality and communication styles in business negotiations. By examining various personality types such as extraverted, introverted, agreeable, conscientious, and neurotic, this study explores how personality characteristics influence communication strategies in the negotiation process. Through surveys and in-depth qualitative analysis of business professionals, the research found that individuals with extraverted personalities tend to be more proactive in taking initiative, whereas introverts are more inclined to deliberate carefully before acting. The communication styles employed also vary based on individual personalities. This research indicates that a deeper understanding of the role of personality in business communication can enhance negotiation effectiveness and improve final outcomes. The practical implications of these findings underscore the importance of adapting communication strategies based on the personality characteristics of negotiation participants to achieve success in dynamic and complex business environments.